2006
DOI: 10.1073/pnas.0603110103
|View full text |Cite
|
Sign up to set email alerts
|

A DNA vaccine targeting angiomotin inhibits angiogenesis and suppresses tumor growth

Abstract: Endogenous angiogenesis inhibitors have shown promise in preclinical trials, but clinical use has been hindered by low half-life in circulation and high production costs. Here, we describe a strategy that targets the angiostatin receptor angiomotin (Amot) by DNA vaccination. The vaccination procedure generated antibodies that detected Amot on the endothelial cell surface. Purified Ig bound to the endothelial cell membrane and inhibited endothelial cell migration. In vivo, DNA vaccination blocked angiogenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 34 publications
5
85
1
Order By: Relevance
“…Vaccinated females were then mated with a BALBneuT male and neu C offspring was evaluated for mammary tumor development. We have previously shown that vaccinationinduced anti-Amot antibodies impair tumor vascularization 26 and significantly delay autochthonous tumor progression 27 in female BALB-neuT mice. Post-vaccination anti-Amot antibody induction was confirmed in pAmot-vaccinated mother sera and milk as well as in the sera of their offspring (pAmot offspring) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccinated females were then mated with a BALBneuT male and neu C offspring was evaluated for mammary tumor development. We have previously shown that vaccinationinduced anti-Amot antibodies impair tumor vascularization 26 and significantly delay autochthonous tumor progression 27 in female BALB-neuT mice. Post-vaccination anti-Amot antibody induction was confirmed in pAmot-vaccinated mother sera and milk as well as in the sera of their offspring (pAmot offspring) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunization and tumor growth The pCMV3.1 control and the ECTM, 16 the pcDNA3 and pAmot 26 plasmids were generated as previously described. The pAAV-MCS (control plasmid) and the pAAV-MCS plasmid coding for Escherichia coli b-galactosidase (LacZ plasmid), were from the AAV Helper-Free System (Agilent Technologies Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were vaccinated by electroporation with DNA plasmid coding human p80 Amot (pAmot or Angiomotin) and control pcDNA3 (generated as previously described [37]) when tumor mass reached 4 mm mean diameter and, again, 7 days after. Briefly, 50 μg of plasmid in 20 μl of 0.9% NaCl were injected in the quadriceps muscle of anesthetized mice n = 6 for both treated (Angiomotin plasmid) and untreated (pcDNA3 plasmid) groups, respectively.…”
Section: Contrast Agentmentioning
confidence: 99%
“…Indeed, the possibility of generating a long-term memory against tumor cell antigens following postsurgical vaccination was shown in colorectal cancer patients immunized with the carcinoembryonic antigen, in which the titer of antibodies 24 months after the last vaccination correlated with longer survival (Ullenhag et al, 2004). Vaccination with the intent of preventing tumor angiogenesis has been performed by targeting various endothelial cell antigens, including VEGFR2, angiomotin and platelet-derived growth factor receptorb (Niethammer et al, 2002;Holmgren et al, 2006;Kaplan et al, 2006). In this context, DLL4 represents a particularly attractive therapeutic target given the recent recognition of the vital role for endothelial tip cells in organizing the formation of the angiogenic sprout (Hellstrom et al, 2007;Suchting et al, 2007).…”
Section: Inhibition Of Tumor Growth Is Mediated By a Humoral Responsementioning
confidence: 99%